Social Maturity: Resource Approach to the Explication of Personality Competence - Omelchuk, Alexander (Psychological Counseling and Psychotherapy, 2022)
The article is devoted to the theoretical substantiation of social maturity as psychological resource of personality competence. The aim of the represented material is theoretical explication of the problem of social maturity of a personality as the resource approach to the interpretation of personality competence. The method of psychological reconstruction as theoretical study of subjective architecture of the phenomenon of social maturity in the perspective of identifying the methodological potentialities of each component of the resource approach is laid on the basis.The results include theoretical analysis of the basic positions of the study of social maturity of personality and outlining the methodological interpretation in the systemic, personalityactivity, synergetic and acmeological concepts.The subjective doctrine of analysis of the stated problem allows to unite the basic ppositions of consideration of social maturity as personality competence with the attraction to the basic social abilities and mobilization of psychological resources of personality. The theoretical scheme of manifestation of social maturity within the resource potentialities of personality competence is suggested.Two methodological orientations (result orientation and uniqueness orientation), which determine the manifestation of this phenomenon by signs of external and internal motivation; the types of external and internal psychological resources are singled out, which together determine the "potential of competence" in the whole set of systemic-synergetic integrity of manifestation of self-realization of personality as a subject of social activity.It is substantiated that axiological, reflexive and anticipatory mechanisms of functioning are involved in the potential of competence of social maturity.The conclusions indicate that the proposed theoretical scheme of social maturity manifestation within the resource potentialities of personality competence can be successfully used in the applied proceedings of preventive and developmental psychotechnologies, taking into account the social status, socio-cultural development, sex and gender models of behavior of a personality.